Retrofit of water network with regeneration using water pinch analysis - Tan, Y. L.; Abdul Manan, Zainuddin; Foo, D. C. Y. (Elsevier B.V., 2007)
This paper presents the development of a new systematic technique for the retrofit of water network with regeneration based on water pinch analysis. The procedure consists of two parts: retrofit targeting and design for a water network with regeneration unit(s). In the targeting stage, retrofit targets (utility savings and capital investment) were determined for a range of process parameters (total flowrate and/or outlet concentration of the regeneration unit) to obtain a savings versus investment curve. Next, the existing water network was re-designed to meet the chosen targets. A case study on paper making process was used to demonstrate the new methodology.